Performance analysis and dynamic characteristics of a proton exchange membrane fuel cell with dual recirculation pumps for air-free applications - Liu, Yang (2023)
The exhaust gas recirculation strategy is usually used to ensure the stable and continuous operation of hydrogen–oxygen proton exchange membrane fuel cells (H2/O2 PEMFCs). However, few studies have focused on how the operating conditions of recirculation pumps affect the dynamic characteristics and performance of H2/O2 PEMFCs. In this study, a PEMFC system with dual anodic and cathodic gas recirculation pumps is investigated and the dynamic performance of the stack is also studied. The pump mode is proven to alleviate water flooding and enhance the stack performance effectively. When the rotating speed of recirculation pump reaches 5000 revolutions per minute, it can increase the gas flow rate inside the stack channel to 0.44 m s−1 (equivalent to a stoichiometric ratio of 2.85), which terminates the low-velocity flow inside the H2/O2 PEMFC and facilitates the removal of liquid water inside the stack. Moreover, the voltage undershoot during the current loading process is moderated by increasing the intake flow rate of the fuel gas through the pump-based recirculation subsystem, which could effectively solve the gas shortage problem of the stack. The presented findings are expected to provide more insights into the impact of the gas recirculation strategy on the performance of high-power stacks.